Cerebellar function and ischemic brain lesions in migraine patients from the general population. (February 2017) - Koppen, Hille; Boele, Henk-Jan; Palm-Meinders, Inge H; Koutstaal, Bastiaan J; Horlings, Corinne GC; Koekkoek, Bas K; van der Geest, Jos; Smit, Albertine E; van Buchem, Mark A; Launer, Lenore J; Terwindt, Gisela M; Bloem, Bas R; et al.
Objective: The objective of this article is to obtain detailed quantitative assessment of cerebellar function and structure in unselected migraine patients and controls from the general population. Methods: A total of 282 clinically well-defined participants (migraine with aura n  = 111; migraine without aura n  = 89; non-migraine controls n  = 82; age range 43–72; 72% female) from a population-based study were subjected to a range of sensitive and validated cerebellar tests that cover functions of all main parts of the cerebellar cortex, including cerebrocerebellum, spinocerebellum, and vestibulocerebellum. In addition, all participants underwent magnetic resonance imaging (MRI) of the brain to screen for cerebellar lesions. As a positive control, the same cerebellar tests were conducted in 13 patients with familial hemiplegic migraine type 1 (FHM1; age range 19–64; 69% female) all carrying a CACNA1A mutation known to affect cerebellar function. Results: MRI revealed cerebellar ischemic lesions in 17/196 (8.5%) migraine patients and 3/79 (4%) controls, which were always located in the posterior lobe except for one control. With regard to the cerebellar tests, there were no differences between migraine patients with aura, migraine patients without aura, and controls for the: (i) Purdue-pegboard test for fine motor skills (assembly scores p  = 0.1); (ii) block-design test for visuospatial ability (mean scaled scores p  = 0.2); (iii) prism-adaptation task for limb learning (shift scores p  = 0.8); (iv) eyeblink-conditioning task for learning-dependent timing (peak-time p  = 0.1); and (v) body-sway test for balance capabilities (pitch velocity score under two-legs stance condition p  = 0.5). Among migraine patients, those with cerebellar ischaemic lesions performed worse than those without lesions on the assembly scores of the pegboard task ( p  < 0.005), but not on the primary outcome measures of the other tasks. Compared with controls and non-hemiplegic migraine patients, FHM1 patients showed substantially more deficits on all primary outcomes, including Purdue-peg assembly ( p  < 0.05), block-design scaled score ( p  < 0.001), shift in prism-adaptation ( p  < 0.001), peak-time of conditioned eyeblink responses ( p  < 0.05) and pitch-velocity score during stance-sway test ( p  < 0.001). Conclusions: Unselected migraine patients from the general population show normal cerebellar functions despite having increased prevalence of ischaemic lesions in the cerebellar posterior lobe. Except for an impaired pegboard test revealing deficits in fine motor skills, these lesions appear to have little functional impact. In contrast, all cerebellar functions were significantly impaired in participants with FHM1.